Eight-year results of transtibial nonanatomic single-bundle versus double-bundle anterior cruciate ligament reconstruction: Clinical, radiologic outcomes and survivorship. (5th April 2019) - Yoon, Kyoung Ho; Kim, Jung Suk; Kim, Sang Jun; Park, Moonsu; Park, Soo Yeon; Park, Sang Eon
Purpose: To compare the long term outcomes of transtibial nonanatomic single-bundle (SB) and double-bundle (DB) anterior cruciate ligament (ACL) reconstruction. Methods: Between January 2008 and September 2010, we retrospectively evaluated 377 patients who underwent primary ACL reconstruction and who were available at 8 years of follow-up. Patients who received transtibial nonanatomic SB ACL reconstruction ( n = 263) were assigned to group SB and DB ACL reconstruction ( n = 114) to group DB. The patients were assessed with the International Knee Documentation Committee (IKDC), the Lysholm scores, Tegner activity score, knee joint stability tests, and patellofemoral osteoarthritis (OA) findings using the Kellgren–Lawrence (K-L) classification. Contralateral ACL (CACL) injury was also evaluated. Results: Thirteen patients underwent revision ACL surgery during the follow-up. Ultimately, 256 patients in group SB and 108 patients in group DB were available at the 8-year follow-up. At final follow-up, the IKDC subjective score ( p = 0.04) and Lysholm score ( p = 0.02) showed significantly superior results in group DB compared to group SB. However, there was no significant difference of Tegner activity score ( p = 0.30), range of motion ( p = 0.81), and knee joint stability tests. There was significant progression of patellofemoral OA between preoperative and final follow-up in ipsilateral knee of both groups but not significant progression in contralateral knee. However, there was no significant difference between the two groups at the follow-up. There were 2.7% ipsilateral ACL graft failure in group SB, compared with 5.2% in group DB ( p = 0.12) and 6.4% CACL tear in group SB, compared with 5.2% in group DB ( p = 0.65). The mean survivorship of ACL graft was 9.47 ± 0.05 years (95% confidence interval (CI), 9.36–9.58) in group SB and 9.87 ± 0.16 years (95% CI, 9.54–10.20) in group DB, and there was no significant difference ( p = 0.25). Conclusion: DB ACL reconstruction resulted in significantly better clinical IKDC subjective scores and Lysholm scores. However, most of the differences in clinical scores were small, and the clinical relevance of this difference is unknown. In addition, there was no significant difference in Tegner activity score, knee joint stability tests, patellofemoral OA, and survivor rate of the ACL graft and CACL after reconstruction after a minimum of 8-year follow-up. Level of Evidence: Cohort study; level of evidence, 3.